E-commerce in India: Trends, Hurdles, and Growth Opportunities - Fatima Akther (PT FORMOSA CENDEKIA GLOBAL, 2023)
India's e-commerce future looks promising thanks to rapid tech advancements and shifting consumer behavior. The study dissects upcoming trends, challenges, and opportunities in India's e-commerce scene. It examines how consumer preferences are evolving due to increased smartphone and internet adoption, pivotal factors driving e-commerce growth. Notable trends include the dominance of online shopping, the rise of mobile commerce, and the emergence of social shopping. Furthermore, it highlights formidable challenges faced by the industry, including resource limitations, complex infrastructure needs, regulatory hurdles, and intense competition. The paper suggests strategies to address these challenges. It also underscores the importance of personalized customer experiences, sustainable practices, and cross-border e-commerce for growth and differentiation in India's e-commerce landscape. Ultimately, this paper aims to guide India's e-commerce future by navigating these growth paths, addressing challenges, and seizing opportunities. It provides crucial insights for e-commerce businesses, policymakers, and investors looking for lucrative prospects. Understanding this rapidly evolving market empowers stakeholders to make informed decisions and contribute to India's thriving e-commerce ecosystem.